Trust-based selling : finding and keeping customers for life - David A Monty (Springer, 2015)
The first year of developing a new sales territory or establishing new customers is a daunting task?especially in dog-eat-dog industries. The traditional advice is to train quickly on products, grab a customer list, start calling for appointments, discover opportunities, and close deals. In fact, almost every sales model out there is based on nothing more than "opportunity" management. But jumping straight to opportunity will leave salespeople chasing their tails and coming up short on payday. With an emphasis on basic sales skills that have been refreshed for today's generation of buyers, Trust-Based Selling shows there is a significant problem you must overcome when opening up new accounts and territories. No matter what you are selling, your prospect already has a trusted relationship with an incumbent vendor and will continue to buy from that vendor even when you have the better solution. The playing field is not level?and you?re on the wrong side. So how can you compete to win? "Trust is the grease that makes business sales effortless," writes sales pro and trainer Dave Monty in this quick-read book. Opportunity metrics are important, but trust?and a few sharp insider tactics Monty reveals?is the guidepost that leads to success.